2016
DOI: 10.1080/13811118.2016.1162238
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Behavioral Therapy for Veterans with Depression and Suicidal Ideation

Abstract: The current study examined suicidal ideation (SI) and depression outcomes among Veterans receiving Cognitive Behavioral Therapy for depression (CBT-D) throughout the Department of Veterans Affairs health care system. Patient outcomes included Beck Depression Inventory-II total score and SI item. Of 902 patients, 427 (47%) had no SI, 405 (45%) had SI but no suicidal intent, 26 (3%) indicated suicidal desire, 8 (1%) indicated suicide intent if they had the chance, and 36 (4%) did not answer this question at sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…Results revealed that interpersonal psychotherapy (IPT [10];), but not cognitive behavioral therapy (CBT [11];), reduced rates of suicidal ideation among patients with depression. However, in a more recent study of veterans receiving CBT, rates of suicidality decreased significantly following treatment [12].…”
Section: Introductionmentioning
confidence: 90%
“…Results revealed that interpersonal psychotherapy (IPT [10];), but not cognitive behavioral therapy (CBT [11];), reduced rates of suicidal ideation among patients with depression. However, in a more recent study of veterans receiving CBT, rates of suicidality decreased significantly following treatment [12].…”
Section: Introductionmentioning
confidence: 90%
“…BDI scores also showed clinically significant reductions following CPT treatment. Other studies have reported that Veterans who receive treatment with multiple interventions for PTSD and other trauma-related problems showed significant reductions in suicidal ideation, in addition to other benefits of treatment (Brown et al, 2016;Trockel et al, 2015;Walser et al, 2015). At the system level, VA researchers have documented mental health service and other cost offsets in the range of 30-40 percent associated with the delivery of EBTs for PTSD by trained therapists (Meyers et al, 2013;Tuerk et al, 2013).…”
Section: Veterans Health Administration Ebt Training Programmentioning
confidence: 99%
“…Depression is a common mood disorder, characterised as having high incidence rates of recurrence, disability and suicide [1].The World Psychiatric Association survey showed that the present global incidence of depression is 4.2%, and it is 6.9% in China. Depression is now a serious worldwide public health and social issue affecting patients' physical and mental health and reducing their quality of life.…”
Section: Introductionmentioning
confidence: 99%